2023
DOI: 10.3390/ma16134840
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Potential of Marine Biopolymers: Sources, Classification, and Diverse Food Applications

Ipsheta Bose,
Nousheen,
Swarup Roy
et al.

Abstract: Environmental concerns regarding the usage of nonrenewable materials are driving up the demand for biodegradable marine biopolymers. Marine biopolymers are gaining increasing attention as sustainable alternatives in various industries, including the food sector. This review article aims to provide a comprehensive overview of marine biopolymers and their applications in the food industry. Marine sources are given attention as innovative resources for the production of sea-originated biopolymers, such as agar, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 168 publications
0
4
0
Order By: Relevance
“…Moreover, according to the results of the agar disc-diffusion method, the highest antibacterial activity (higher zone of inhibition) of FXT was exhibited against Streptococcus agalactiae, Staphylococcus epidermidis, and Staphylococcus aureus [87]. In another study, FXT isolated from Turbinaria triquetra showed potential antibacterial activity against both Gram-positive and Gram-negative bacteria within a concentration range of 10-100 µg/mL [88]. FXT, in higher concentrations, showed significant antimicrobial activity against Listeria monocytogenes, Staphylococcus aureus, Enterococcus sp., Bacillus subtilis, and Psuedomonas aeruginosa [89]; however, higher concentrations of phytoconstituents may cause toxicity.…”
Section: Biological Activity Of Carotenoidsmentioning
confidence: 98%
“…Moreover, according to the results of the agar disc-diffusion method, the highest antibacterial activity (higher zone of inhibition) of FXT was exhibited against Streptococcus agalactiae, Staphylococcus epidermidis, and Staphylococcus aureus [87]. In another study, FXT isolated from Turbinaria triquetra showed potential antibacterial activity against both Gram-positive and Gram-negative bacteria within a concentration range of 10-100 µg/mL [88]. FXT, in higher concentrations, showed significant antimicrobial activity against Listeria monocytogenes, Staphylococcus aureus, Enterococcus sp., Bacillus subtilis, and Psuedomonas aeruginosa [89]; however, higher concentrations of phytoconstituents may cause toxicity.…”
Section: Biological Activity Of Carotenoidsmentioning
confidence: 98%
“…Algal biopolymers, especially from seaweed, are often used as food since they are abundant and sometimes especially healthy [ 50 , 51 , 52 ]. On the other hand, they can be used for food packaging due to their nontoxicity and biodegradability [ 53 , 54 , 55 ].…”
Section: Algal Biopolymersmentioning
confidence: 99%
“…Therefore, the green packaging from seafood leftovers can be better exploited to replace their synthetic counterparts . Their nanomaterials in different forms such as fibers, hydrogels, beads, sponges, and membranes have interesting applications in biomedical fields such as surgical sutures, artificial skin, rebuilding of bone, controlled drug delivery, and others. …”
Section: Green Extractions Of Ingredients From Seafood Side Streamsmentioning
confidence: 99%